Structure–mechanism relationship of antioxidant and ACE I inhibitory peptides from wheat gluten hydrolysate fractionated by pH - Cian, Raúl Esteban (2015)
The aims of this study were to assess bioactive properties (ACE inhibition and antioxidant capacity) from wheat gluten hydrolysate peptides fractionated by pH (4.0, 6.0 and 9.0), to determine peptide action mechanism, and to relate it to the secondary structure and functional groups of peptides. Gluten hydrolysate extracts (GHE) were enriched in peptideswith mediumhydrophobicity and molecularweight (≈60%MH and 5.5 kDa, respectively). Gluten peptides inhibited ACE I by uncompetitive mechanism and a direct relationship between α-helix structure and IC50% value was obtained (r = 0.9127). TEAC and cooper chelating activity from GHE 6.5 were the highest and directly correlated with MH peptides. GHE 9.0 had high carotene bleaching inhibition (47.5± 0.3%) and reducing power activity (163.1±2.9 mg S2O3 2 − equivalent g−1 protein), which were directly related to disulfide bonds content of peptides (r=0.9982 and 0.9216, respectively). pHwas a good alternative to select bioactive peptides from wheat gluten hydrolysate.